The dynamic influence of the global financial cycle: synchronization and impact on South Africa’s financial cycle - Khwazi Magubane; Precious Mncayi-Makhanya (Cogent Economics & Finance)
This study investigates the synchronization and impact of the global financial cycle on South Africa’s financial cycle, focusing on the period from 1990 to 2022. Given South Africa’s susceptibility to global financial fluctuations as an emerging market, the research explores how international financial conditions influence domestic financial stability. The study employs a Bayesian Time-Varying Coefficient Vector Autoregression together with key economic indicators such as economic activity, inflation and macroprudential policies which are incorporated to evaluate their changing effects over time. The analysis reveals a strong positive correlation between the global financial cycle and South Africa’s financial cycle, highlighting the significant influence of global financial trends on the country’s financial stability. The effects of economic activity, inflation and macroprudential policies also vary across different time periods, contributing to the shaping of the domestic financial cycle. This study contributes to understanding the global financial cycle’s impact on an emerging market, emphasizing the importance of integrating global financial conditions into domestic economic policy frameworks. The findings provide practical insights for South African policymakers, suggesting that adaptive macroprudential measures and effective management of inflation and capital flows can help mitigate the effects of international shocks and stabilize the financial system.